2020
DOI: 10.2147/jaa.s278119
|View full text |Cite
|
Sign up to set email alerts
|

<p>Characteristics of Asthma-related Nocturnal Cough: A Potential New Digital Biomarker</p>

Abstract: The nature of nocturnal cough is largely unknown. It might be a valid marker for asthma control but very few studies characterized it as a basis for better defining its role and its use as clinical marker. This study investigated prevalence and characteristics of nocturnal cough in asthmatics over the course of four weeks. Methods: In two centers, 94 adult patients with physician-diagnosed asthma were recruited. Patient-reported outcomes and nocturnal sensor data were collected by a smartphone with a chat-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 24 publications
0
8
2
Order By: Relevance
“…Nocturnal cough is highly prevalent in adult patients with asthma [32], and a high frequency of nocturnal cough is shown to be significantly related to the presence of AHR [33]. While our findings confirm the importance of wheezing and nocturnal cough as predictors of AHR, Yavuz et al [10] found that, in spite of a quite similar patient selection, there is neither a significant association of AHR with wheezing nor with nocturnal cough.…”
Section: Association Of Asthma-like Symptoms With Ahrcontrasting
confidence: 59%
“…Nocturnal cough is highly prevalent in adult patients with asthma [32], and a high frequency of nocturnal cough is shown to be significantly related to the presence of AHR [33]. While our findings confirm the importance of wheezing and nocturnal cough as predictors of AHR, Yavuz et al [10] found that, in spite of a quite similar patient selection, there is neither a significant association of AHR with wheezing nor with nocturnal cough.…”
Section: Association Of Asthma-like Symptoms With Ahrcontrasting
confidence: 59%
“…Nocturnal cough is highly prevalent in adult patients with asthma (27) and a high frequency of nocturnal cough is shown to be significantly related to the presence of AHR (28). While our findings confirm the importance of wheezing and nocturnal cough as predictors of AHR, Yavuz et al (7) found that, in spite of a quite similar patient selection, there is neither a significant association of AHR with wheezing nor with nocturnal cough.…”
Section: Association Of Asthma-like Symptoms With Ahrcontrasting
confidence: 58%
“…The main limitation of such approaches is that recording with consistent quality can only be guaranteed under well-defined circumstances (mobile phone openly placed on table or nightstand next to the user) and during certain times of day (at home or in other silent environments). For conditions where, e.g., the nightly cough burden can be used as a surrogate marker for the general patient state, these approaches may be a cost-effective alternative to monitor disease progression (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%